Monocytes of Patients Congenitally Deficient in Plasma Factor XIII Lack Factor XIII Subunit A Antigen and Transglutaminase Activity - Muszbek, László; Ádány, Roza; Kávai, Mária; Boda, Zoltán; Lopaciuk, Stanislaw (Thrombosis and Haemostasis, 1988)
Monocytes isolated from patients with severe deficiency in plasma Factor XIII of blood coagulation (FXIII) were tested for FXIII antigen and transglutaminase activity. By immunoperoxi- dase method the patients’ monocytes, in contrast to normal controls, showed no reaction with a monospecific antibody against FXIII subunit ª.This result was confirmed by immuno- blotting technique, as well. In addition, tissue macrophages tested in one of the patients were also exempt of FXIII subunit ª antigen. The transglutaminase activity in FXIII deficient monocytes was below the limit of the detection of the dansylcadaverine incorporation assay. The results suggest that FXIII subunitªof monocytes/macrophages and its plasma and platelet counterparts are closely related or identical proteins and demonstrate that the transglutaminase activity in monocytes is of FXIII origin and tissue transglutaminase is present, if at all, only in insignificant amount.
Keywords: Factor XIII; Monocytes; Transglutaminase